Preparation of low-temperature and low-bombardment transparent conductive thin film and application of thin film in perovskite / crystalline silicon laminated solar cell

By adopting a low-temperature and low-blasting composite transparent conductive oxide thin film preparation method in perovskite/silicon stacked solar cells, the problem of damage to the absorbent layer under the high-temperature annealing is solved and the high-power density damages the solar cell is achieved, and efficient loading is achieved Improved efficiency of flow transmission and photoelectric conversion.

CN119491195AActive Publication Date: 2025-02-21NANKAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411659739.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-21
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In existing perovskite/silicon stacked solar cells, high-temperature annealing leads to an increase in crystallinity of transparent conductive oxide films, but damages the absorbent layer below; and high power density can also damage the lower layers of the solar cell, and the single layer doping The carrier transmission path of indium zirconium oxide thin film is not conducive to vertical transmission.

Method used

Using the preparation method of low-temperature and low-bombing composite transparent conductive oxide film, the IZrO film with different doping concentrations is deposited at room temperature by magnetron sputtering, and its growth mode is controlled to form columnar and isometric crystallized TCO films, and combined to form composite Thin film, used in perovskite/silicon stacked solar cells as transparent electrodes.

Benefits of technology

The crystallinity and carrier transmission capacity of TCO film at room temperature are improved, the bombardment on the lower layer is reduced, the vertical and lateral transmission of carriers in the solar cell is promoted, and the photoelectric conversion efficiency of the solar cell is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491195A_ABST
    Figure CN119491195A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a low-temperature and low-bombardment transparent conductive film and application of the transparent conductive film in a perovskite / crystalline silicon laminated solar cell. The composite film is prepared by carrying out magnetron sputtering on TCO ceramic targets with different doping proportions at room temperature. And argon-oxygen mixed gas is used as process gas. All deposition is performed before deposition at a base pressure of less than 1 * 10 <-5 > Pa. According to the composite transparent conductive oxide film disclosed by the invention, different growth modes of the composite transparent conductive oxide film are regulated and controlled by regulating and controlling sputtering air pressure and power of the TCO film with different doping proportions, so that the composite transparent conductive oxide film with low temperature and low bombardment is obtained. The lower layer of the composite transparent conductive oxide thin film is in a columnar crystal growth mode, the upper layer of the composite transparent conductive oxide thin film is in an equiaxial large-grain growth mode, the composite transparent conductive oxide thin film can be applied to a perovskite / silicon laminated solar cell, the vertical and transverse transmission capacity of carriers in a TCO transparent electrode can be promoted, effective collection and transmission of carrier charges are promoted, and the photoelectric conversion efficiency is improved. And the high-efficiency perovskite / silicon laminated solar cell is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of transparent conductive oxide film preparation, and in particular to a transparent conductive oxide film and a preparation method and application thereof. Background Art

[0002] At present, the development of perovskite / silicon tandem solar cells faces the challenge of light management, enhancing the transmission of each thin film except the absorption layer of the top cell for a wide spectrum and reducing reflection. Therefore, for perovskite / silicon tandem solar cells, the selection of transparent electrodes is one of the key factors affecting the efficiency of the cell. Transparent conductive oxide (TCO) films have the advantages of good conductivity and high optical transparency in the field of solar cells. At present, the most common TCO film systems include doped SnO2, doped In2O3 and doped ZnO. The most representative of them is doped In2O3 film, including indium tin oxide (ITO) film, indium zinc oxide (IZO) film, indium zirconium oxide (IZrO) film, etc. Among these TCOs, Zr-doped In2O3 has higher carrier mobility due to less electron scattering [IEEE J Photovolt. 2018; 8(5): 1202-1207]. In addition, due to its higher dielectric constant, zirconium-doped In2O3 can shift the plasma frequency to longer wavelengths in the near-infrared region, thereby increasing the transmittance of near-infrared wavelengths. Erkan-Aydin et al. reported that zirconium-doped indium oxide (IZrO) is a promising material for transparent electrodes of perovskite solar cells due to its high transparency and low resistivity [Adv Funct Mater. 2019; 29(25): 1901741]. Thermal annealing can cause phase transition of IZrO thin films and improve their crystallinity. However, due to the damage of high temperature to the lower absorber layer of perovskite / silicon tandem solar cells, it is impossible to thermally anneal the TCO transparent electrode in the tandem device to achieve better performance. Moreover, high power density will also damage the lower layers of the tandem solar cell. In addition, the efficient carrier transport path between the buffer layer and the transparent electrode is noteworthy. The general single-layer zirconium-doped indium oxide (IZrO) transparent electrode prefers to transport carriers laterally in equiaxed grains, which will hinder the vertical transport of carriers from the buffer layer to the upper layer [Sol.RRL. 2024; 8(6): 2301029]. Therefore, the concept of stacking composite transparent conductive oxide films with different growth modes was introduced to maximize the crystallinity of TCO films prepared at room temperature. The small sputtering power of the first layer of the composite film can also reduce the bombardment of the lower layer of the device. Therefore, the introduction of composite TCO transparent electrodes in perovskite / silicon stacked solar cells promotes the vertical and lateral transport of carriers in solar cells, and promotes the effective collection and transport of carrier charges. Summary of the invention

[0003] The purpose of the present invention is to solve the above problems existing in the prior art and to provide a low-temperature, low-bombardment composite transparent conductive film and a preparation method and application thereof.

[0004] The technical solution adopted by the present invention is:

[0005] First, the present invention provides a method for preparing a low-temperature, low-bombardment composite transparent conductive film, comprising the following steps:

[0006] 1) Using argon-oxygen mixed gas as the reaction gas, magnetron sputtering deposition was used to deposit IZrO thin films with different doping concentrations on a substrate at room temperature, and its growth mode was controlled to obtain two TCO thin films with different crystallization modes, which is beneficial to the longitudinal and lateral transport of carriers in the thin film;

[0007] 2) Combining two TCO films with different crystallization modes into a composite film and applying it as a transparent electrode in perovskite / silicon tandem solar cells to improve the vertical and lateral transport capabilities of carriers in solar cells;

[0008] In step 1), before sputtering, the substrate is cleaned in an acetone and isopropanol ultrasonic bath, and In2O3:ZrO2=95wt%:5wt% and In2O3:ZrO2=98wt%:2wt% IZrO ceramic targets are selected for sputtering, for a single-layer IZrO film, a 2wt% Zr-doped IZrO target is selected for sputtering, and for a composite IZrO film, 5wt% and 2wt% Zr-doped IZrO targets are selected for sputtering, respectively;

[0009] The different crystal modes are columnar crystal and equiaxed crystal.

[0010] Furthermore, in step 1), the temperature of the substrate is room temperature.

[0011] Step 1) The reaction gas is a 3% argon-oxygen mixture; wherein the O partial pressure X = O2 / (Ar+O2)%, when X = 0.06%, the sputtering power is adjusted to start depositing the IZrO film at a deposition rate of ~0.4nm / min; the sputtering power is 25W-50W; preferably, 25W, 30W, 35W, 40W, 45W, 50W.

[0012] Step 1) The deposited TCO films with different doping ratios have different crystallization modes, wherein the 5wt% Zr-doped IZrO film deposited at 1.2mtorr and a sputtering power of 35W tends to be columnar crystallized, and the 2wt% Zr-doped IZrO film sputtered at 0.9motrr and a sputtering power of 45W tends to be equiaxed crystallized.

[0013] The sputtering pressure of the deposited TCO film in step 1) has different crystallization modes; wherein the sputtering pressure is 0.6mtorr-1.5mtorr; preferably, 0.6mtorr, 0.9mtorr, 1.2mtorr, 1.5mtorr.

[0014] Furthermore, the composite transparent conductive oxide film in step 2) needs to be prepared at low bombardment, and the lower layer of the composite film needs to be prepared at low power.

[0015] Step 2) The composite transparent conductive oxide film is prepared with different crystalline layer thickness ratios to obtain a mobility of 20 cm 2 ·V -1 ·s -1 ~50cm 2 ·V -1 ·s -1 , the carrier concentration is 3×10 20 cm -3 ~1×10 21 cm -3 .

[0016] Step 2) The composite transparent conductive oxide film is adjusted to have a thickness ratio of different crystal layers to obtain a sheet resistance of ≤30Ωsq -1 .

[0017] Step 2) The composite transparent conductive oxide film has good transmittance in the visible light and near infrared bands of 400-1200nm, with an average transmittance of ≥80%.

[0018] The present invention also provides the use of the low-temperature, low-bombardment transparent conductive film obtained by the above preparation method in perovskite / crystalline silicon tandem solar cells. The TCO composite transparent conductive film is applied to perovskite / silicon tandem solar cells as a transparent electrode to promote the improvement of the vertical and lateral transmission capabilities of carriers in the solar cell, and has good optical transmittance, thereby obtaining a high-efficiency perovskite / silicon tandem solar cell.

[0019] Advantages and positive effects of the present invention: The present invention proposes the concept of a composite transparent conductive film to maximize the crystallinity of the TCO film prepared at room temperature, and the small sputtering power of the first layer of the composite film can also reduce the bombardment of the lower layer of the device, so a composite TCO transparent electrode is introduced into the stacked solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the perovskite / silicon tandem solar cell used in the present invention.

[0021] Figure 2 Schematic diagram of the carrier transport path of the equiaxed TCO film as the transparent front electrode of the stacked device.

[0022] Figure 3 Schematic diagram of the carrier transport path of the columnar TCO film as the transparent front electrode of the stacked device.

[0023] Figure 4 FoM (FoM = T 10 / R sq )parameter.

[0024] Figure 5 Carrier mobility (μ), carrier concentration (N) and sheet resistance (R) of IZrO films prepared by sputtering at different gas pressures sq ).

[0025] Figure 6 is the sheet resistance (R) of the composite transparent conductive IZrO film at different thickness ratios sq ).

[0026] Figure 7 JV curve of a single-layer transparent conductive IZrO film as the transparent front electrode of a stacked device.

[0027] Figure 8 JV curve of the composite transparent conductive IZrO film as the transparent front electrode of the stacked device. DETAILED DESCRIPTION

[0028] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0029] Embodiment 1:

[0030] In this embodiment, a zirconium-doped indium oxide (IZrO) thin film is deposited on a glass substrate by magnetron sputtering.

[0031] 1) Before sputtering, the substrate was cleaned in an acetone and isopropanol ultrasonic bath for 10 minutes. In2O3:ZrO2=95wt%:5wt% and In2O3:ZrO2=98wt%:2wt% IZrO ceramic targets were selected for sputtering. For single-layer IZrO films, 2wt% Zr-doped IZrO targets were selected for sputtering, and their parameters were adjusted. For composite IZrO films, 5wt% and 2wt% Zr-doped IZrO targets were selected for sputtering, and their process parameters were adjusted. The basic vacuum pressure of the chamber was less than 1×10 -5 Pa, the distance between substrate and target was kept at 190 mm.

[0032] 2) Place the cleaned glass substrate into the magnetron sputtering system, and place the chamber under a vacuum pressure of less than 1×10 - 5After Pa, an IZrO ceramic target with In2O3:ZrO2=98wt%:2wt% was selected for sputtering. During sputtering, 100sccm of argon was first introduced to start, and the sputtering power was set to 40W. After successful ignition, argon and oxygen were introduced as reaction gases. The volume percentage of oxygen in the reaction gas was 3%. The substrate (glass) temperature was set to room temperature, and the O partial pressure (X=O2 / (Ar+O2)%) during the sputtering process was adjusted. When X=0.06%, the sputtering power was adjusted to 25W, 30W, 35W, 40W, 45W, and 50W, respectively, to start depositing the IZrO film. The deposition rate was controlled to be ~0.4nm / min, and the deposition thickness was 100nm to obtain a deposited film.

[0033] 3) Compare the photoelectric performance by comparing the FoM parameters of IZrO films at different sputtering powers, FoM = T 10 / R sq ), where T is the average transmittance of the band, R sq The best photoelectric performance was obtained at 35W and 45W ( Figure 4 ). However, high power density will damage the underlying layers of the tandem solar cell due to bombardment, and the surface will be rougher.

[0034] Embodiment 2:

[0035] 1) Place the cleaned glass substrate into the magnetron sputtering system, and place the chamber under a vacuum pressure of less than 1×10 - 5 After Pa, In2O3:ZrO2=98wt%:2wt%IZrO ceramic target was selected for sputtering. During sputtering, 100sccm argon was introduced to start, and the sputtering power was set to 40W. After successful ignition, argon and oxygen were introduced as reaction gases. The volume percentage of oxygen in the reaction gas was 3%. The substrate (glass) temperature was set to room temperature, and the deposition pressure was controlled to be 0.6mtorr, 0.9mtorr, 1.2mtorr and 1.5mtorr respectively. Figure 5 As shown, when the sputtering pressure is 0.9 mtorr, the IZrO film sputtered at 0.9 motrr has a 27.7 cm 2 ·V -1 ·s -1 The higher mobility and carrier concentration of 4.3×10 20 cm -3 , tending to be equiaxed crystallization. The mobility of the IZrO film deposited at 1.2 mtorr is 15.7 cm 2 ·V -1 ·s -1 , the carrier concentration reaches 7×1020 cm -3 , tending to be columnar crystals. R of IZrO films sputtered at 0.9 mtorr sq As low as 40.3Ωsq -1 , the Rsq of the IZrO film deposited at 1.2 mtorr is 43.6 Ωsq -1 .

[0036] Embodiment 3:

[0037] The 5wt% Zr-doped IZrO film deposited at 1.2mtorr and a sputtering power of 35W tends to be columnar. The 2wt% Zr-doped IZrO film sputtered at 0.9motrr and a sputtering power of 45W tends to be equiaxed. Figure 6 As shown in Figure 2, when the total thickness is controlled to be 130nm and the thickness ratio of the lower columnar crystal layer to the upper equiaxed crystal layer is 55:75nm, the IZrO film obtains the best electrical and optical properties, and the sheet resistance is as low as 25.55Ω·sq -1 .

[0038] Embodiment 4:

[0039] 1) The structure of the perovskite / silicon tandem solar cell in this embodiment is as follows Figure 1 As shown, from bottom to top, it includes:

[0040] Metal grid electrode silver (Ag), transparent conductive oxide film-tin-doped indium oxide (ITO), p-type doped amorphous silicon (pa-Si:H), intrinsic passivation layer (ia-Si:H), n-type velvet substrate (n-type wafer), intrinsic passivation layer (ia-Si:H), n-type doped amorphous silicon (na-Si:H), n-type doped nanocrystalline silicon (n-nc-Si:H), p-type doped nanocrystalline silicon (p-nc-Si:H), Spiro-TTB at <6.5×10 -6 mbar working pressure One-step spin coating deposition of the perovskite absorber layer at a rate of <2×10 -6 mbar working pressure, Evaporation rate 15nm C 60 , using 20nm SnO2 prepared by atomic layer deposition (ALD) as the buffer layer, and a 130nm 2wt% Zr-doped IZrO transparent electrode prepared by magnetron sputtering with a sputtering power of 45W, X=0.06% (X=O2 / (Ar+O2)%), and a sputtering pressure of 0.9mtorr.

[0041] 2) The open circuit voltage of the solar cell prepared in this example is 1876mV and the short circuit current density is 19.72mA / cm2 , fill factor 75.57%, photoelectric conversion efficiency 27.95%; reverse scan open circuit voltage 1851mV, short circuit current density 19.70mA / cm 2 , fill factor 73.34%, photoelectric conversion efficiency 26.75% ( Figure 7 ).

[0042] Embodiment 5:

[0043] 1) The structure of the perovskite / silicon tandem solar cell in this embodiment is as follows Figure 1 As shown, from bottom to top, it includes:

[0044] Metal grid electrode silver (Ag), transparent conductive oxide film-tin-doped indium oxide (ITO), p-type doped amorphous silicon (pa-Si:H), intrinsic passivation layer (ia-Si:H), n-type velvet substrate (n-type wafer), intrinsic passivation layer (ia-Si:H), n-type doped amorphous silicon (na-Si:H), n-type doped nanocrystalline silicon (n-nc-Si:H), p-type doped nanocrystalline silicon (p-nc-Si:H), Spiro-TTB at <6.5×10 -6 mbar working pressure One-step spin coating deposition of the perovskite absorber layer at a rate of <2×10 -6 mbar working pressure, Evaporation rate 15nm C 60 , using 20nm SnO2 prepared by atomic layer deposition (ALD) as a buffer layer, the first layer of ~55nm prepared by magnetron sputtering is 1.2mtorr, 5wt% Zr-doped IZrO film deposited at a sputtering power of 35W, and the second layer of ~75nm is 0.9mtorr, 2wt% Zr-doped IZrO film sputtered at a sputtering power of 45W to form a composite IZrO transparent electrode.

[0045] 2) The open circuit voltage of the solar cell prepared in this example is 1902mV and the short circuit current density is 19.64mA / cm 2 , fill factor 78.61%, photoelectric conversion efficiency 29.37%; reverse scan open circuit voltage 1885mV, short circuit current density 19.64mA / cm 2 , fill factor 76.77%, photoelectric conversion efficiency 28.43% ( Figure 8 ).

[0046] Based on the above embodiments, the present invention provides a method for preparing a low-temperature, low-bombardment transparent conductive film, and provides the application of the obtained transparent conductive film in a perovskite / crystalline silicon tandem solar cell. At the same time, the factors affecting the growth crystallization mode of transparent conductive oxide films on the carrier transport and collection of perovskite / silicon solar cells, the factors affecting the crystallization mode of transparent conductive oxide films, and the factors affecting the crystallization growth mode of TCO are studied.

[0047] First, the effect of the crystallization mode of transparent conductive oxide film growth on carrier transport and collection in perovskite / silicon solar cells was determined.

[0048] Figure 1 This is a schematic diagram of the perovskite / silicon tandem solar cell we use. Figure 2 The schematic diagram of the structure and carrier transport path of the equiaxed TCO film as the transparent front electrode of the stacked device. Figure 2 As shown in Figure 2, carriers do not have good vertical transport capabilities in equiaxed crystalline TCO films. Therefore, when carriers are transferred from the buffer layer to the equiaxed TCO transparent electrode, some of the carriers will be trapped in the grain boundaries. Figure 3 Schematic diagram of the carrier transport path of columnar TCO film as transparent front electrode of stacked device. Columnar crystalline IZrO film has good vertical transport capability, but the carrier mobility is low and cannot be effectively collected by the metal electrode. Therefore, a transparent front electrode with good vertical and lateral transport capabilities is crucial in perovskite / silicon stacked solar cells.

[0049] Secondly, the factors that affect the crystallization mode of transparent conductive oxide films were determined, including: the proportion of doping elements in In2O3, sputtering gas pressure, sputtering oxygen partial pressure, sputtering power, etc.

[0050] Based on previous research results, TCO with a higher doping ratio is more inclined to columnar crystals, while TCO with a moderately low doping ratio is more inclined to equiaxed crystals [J Electroceram. 2009; 23: 169-174].

[0051] Secondly, it is necessary to determine the effect of working pressure on the crystallization pattern of transparent conductive oxide thin films during the coating process. The working pressure affects the number of gas ions bombarding the target in the chamber. The higher the pressure, the more ions are sputtered, which affects the sputtering rate, and the particles have less growth space and tend to be columnar crystals; similarly, when the pressure is lower, the sputtered ions have more growth space and tend to be equiaxed crystals.

[0052] The oxygen-argon flow ratio determines whether the film is in an oxygen-deficient or oxygen-rich environment during the film preparation process, and determines the oxygen vacancy concentration in the film, thereby affecting the electrical properties of the film such as carrier concentration and mobility.

[0053] The sputtering power is related to the sputtering rate during film preparation and the bombardment of the underlying layer. The sputtering rate increases with the increase of power, and the square resistance decreases, but it is easy to cause an oxygen deficiency reaction, resulting in reduced permeability, and needs to be coordinated and controlled with the oxygen and argon flow rates.

[0054] Third, we identified the factors that affect the TCO crystal growth pattern. We combined columnar crystal TCO films and equiaxed crystal TCO films to form a composite transparent conductive oxide film, which was applied to perovskite / silicon solar cells.

[0055] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a low-temperature, low-bombardment transparent conductive film, characterized in that: The following steps are involved: 1) Using argon-oxygen mixed gas as the reaction gas, magnetron sputtering deposition was used to deposit IZrO thin films with different doping concentrations on a substrate at room temperature, and its growth mode was controlled to obtain two TCO thin films with different crystallization modes, which is beneficial to the longitudinal and lateral transport of carriers in the thin film; 2) Combining two TCO films with different crystallization modes into a composite film and applying it as a transparent electrode in perovskite / silicon tandem solar cells to improve the vertical and lateral transport capabilities of carriers in solar cells; In step 1), before sputtering, the substrate is cleaned in an acetone and isopropanol ultrasonic bath, and In2O3:ZrO2=95wt%:5wt% and In2O3:ZrO2=98wt%:2wt% IZrO ceramic targets are selected for sputtering, for a single-layer IZrO film, a 2wt% Zr-doped IZrO target is selected for sputtering, and for a composite IZrO film, 5wt% and 2wt% Zr-doped IZrO targets are selected for sputtering, respectively; The different crystal modes are columnar crystal and equiaxed crystal.

2. The preparation method according to claim 1, characterized in that: Step 1) The temperature of the substrate is room temperature.

3. The preparation method according to claim 1, characterized in that: Step 1) The reaction gas is a 3% argon-oxygen mixture; wherein the O partial pressure X = O2 / (Ar+O2)%, when X = 0.06%, the sputtering power is adjusted to start depositing the IZrO film at a deposition rate of ~0.4nm / min; the sputtering power is 25W-50W; preferably, 25W, 30W, 35W, 40W, 45W, 50W.

4. The preparation method according to claim 1, characterized in that: Step 1) The deposited TCO films with different doping ratios have different crystallization modes, wherein the 5wt% Zr-doped IZrO film deposited at 1.2mtorr and a sputtering power of 35W tends to be columnar crystallized, and the 2wt% Zr-doped IZrO film sputtered at 0.9motrr and a sputtering power of 45W tends to be equiaxed crystallized.

5. The preparation method according to claim 1, characterized in that: The sputtering pressure of the deposited TCO film in step 1) has different crystallization modes; wherein the sputtering pressure is 0.6mtorr-1.5mtorr; preferably, 0.6mtorr, 0.9mtorr, 1.2mtorr, 1.5mtorr.

6. The preparation method according to claim 1, characterized in that: Step 2) The composite transparent conductive oxide film needs to be prepared at low bombardment, and the lower layer of the composite film needs to be prepared at low power.

7. The preparation method according to claim 1, characterized in that: Step 2) The composite transparent conductive oxide film is prepared with different crystalline layer thickness ratios to obtain a mobility of 20 cm 2 ·V -1 ·s -1 ~50cm 2 ·V -1 ·s -1 , the carrier concentration is 3×10 20 cm -3 ~1×10 21 cm -3 .

8. The preparation method according to claim 1, characterized in that: Step 2) The composite transparent conductive oxide film is adjusted to have a thickness ratio of different crystal layers to obtain a sheet resistance of ≤30Ωsq -1 .

9. The preparation method according to claim 1, characterized in that: Step 2) The composite transparent conductive oxide film has good transmittance in the visible light and near infrared bands of 400-1200nm, with an average transmittance of ≥80%.

10. Application of the low-temperature, low-bombardment transparent conductive film obtained by the preparation method according to any one of claims 1 to 9 in perovskite / crystalline silicon tandem solar cells, characterized in that: The TCO composite transparent conductive film is applied to perovskite / silicon tandem solar cells as a transparent electrode, which promotes the improvement of the vertical and lateral transport capabilities of carriers in the solar cells and has good optical transmittance, thereby obtaining a high-efficiency perovskite / silicon tandem solar cell.

Citation Information

Patent Citations

  • SHJ solar cell double-layer TCO film structure and preparation method thereof

    CN114361267A

  • ITO(indium tin oxide) film for transparent electrode manufactured using low frequency sputtering apparatus, and method thereof

    KR1020090069886A

  • Giant magnetostrictive material and manufacturing method thereof, and magnetostrictive actuator and magnetostrictive sensor therewith

    US20010018938A1

  • Transparent conductive oxide thin film and application thereof

    US20230377767A1